Learning Names for RFID-Tagged Objects in Activity Videos - Perera, Ian; Allen, James (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
We describe a method for determining the names of RFID-tagged objects in activity videos using descriptions which have been parsed to provide anaphoric reference resolution and ontological categorization.